A mechanical mungbean sheller for small scale applications - Gallegos, Ralph Kristoffer B. (Philippine agricultural mechanization journal)
A mechanical mungbean sheller prototype was fabricated to address the need of small scale mungbean producing areas of a low capacity mungbean sheller. The prototype was composed of a cylinder-concave assembly as the shelling unit and a blower-screen assembly as the cleaning unit. The sheller is made of locally available materials and powerd by a 1-hp electric motor. It requires one operator whose primary task is to load the mungbean pods into the hopper. The sheller's operating and performance characteristics were established using mungbean pods at MCI = 10.7 percent wb, MC2 = 12.8 percent wb and MC3 = 18.9 percent wb moisture levels. The highest shelling efficiency (98.6 percent) and shelling recovery (96.4 percent) were obtained at the MC1 pod moisture level while the lowest efficiency (96.6 percent) and recovery (93.0 percent) were observed at the MC2 moisture level. The shelling capacity ranged from 19.5 kg/hr (MC3) to 36 kg/hr (MC1), depending on the moisture content of the input pods. MC1 and MC2 pod moisture levels exhibited the highest output purity of 97.3 percent while a lower purity of 94.8 percent was observed using MC3 pods. Mechanically damaged kernels were estimated at a lowest of 5.9 percent at the MC1 level while the highest value of 11.3 percent was noted in MC3 level. Based on the results of the various tests, it is recommended that further studies should be performed to determine the optimum performance characteristics of the sheller.